2021
DOI: 10.1002/clc.23704
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atrial mechanical function on age‐dependent presentation of neurocardiogenic syncope

Abstract: Background: The contribution of atrial and ventricular function in neurocardiogenic syncope (NCS) pathophysiology is elusive.Hypothesis: We assessed the influence of echocardiographic properties to the age of presentation and NCS recurrences. Methods:We assigned 124 patients with symptoms suggesting NCS, to those with syncope initiation at age <35 (group A, n = 56) and >35 years (group B, n = 68). Echocardiographic indices were measured before head-up tilt test (HUTT).Results: A total of 55 had positive HUTT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…This results in a decrease in systemic blood pressure due to reduced venous return as in CAS 23. Consistent with our findings, previous studies have shown that lower LA volume was associated with the development of hypotension in patients with vasovagal syncope 5 6. Patients with LAVI ≥36 mL/m 2 did not experience fainting during a head-up tilt test 6.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This results in a decrease in systemic blood pressure due to reduced venous return as in CAS 23. Consistent with our findings, previous studies have shown that lower LA volume was associated with the development of hypotension in patients with vasovagal syncope 5 6. Patients with LAVI ≥36 mL/m 2 did not experience fainting during a head-up tilt test 6.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the cut-off value of 33.5 mL/m 2 for LAVI in the present study is considered reasonable. More aggressive hydration management has been reported to be preferable for these patients in vasovagal syncope 5. In addition, preoperative hydration was more common in the no-PH group than in the PH group in our study, and thus this intervention may be useful for preventing PH after CAS.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In a recent study, Sotiriadou et al 23 . (2021) compared LA phasic function assessed by 2D STE in patients with VVS divided into two groups of more than 35 years old and less than 35 years old.…”
Section: Discussionmentioning
confidence: 99%